Allometric equations for estimating tree biomass in restored mixed-species Atlantic Forest stands - Nogueira Junior, Lauro Rodrigues; Engel, Vera Lex [UNESP]; Parrotta, John A.; Melo, Antonio Carlos Galvão de; Ré, Danilo Scorzoni [UNESP] (Revista Biota Neotropica, 2014)
Restoration of Atlantic Forests is receiving increasing attention because of its role in both biodiversity conservation and carbon sequestration for global climate change mitigation. This study was carried out in an Atlantic Forest restoration project in the south-central region of Sao Paulo State - Brazil to develop allometric equations to estimate tree biomass of indigenous tree species in mixed plantations. Above and below-ground biomass (AGB and BGB, respectively), stem diameter (DBH: diameter at 1.3 m height), tree height (H: total height) and specific wood density (WD) were measured for 60 trees of 19 species. Different biomass equations (linear and nonlinear-transformed) were adjusted to estimate AGB and BGB as a function of DBH, H and WD. For estimating AGB and BGB, the linear biomass equation models were the least accurate. The transformed nonlinear biomass equation that used log DBH2, log H and log WD as predictor variables were the most accurate for AGB and the transformed nonlinear biomass equations that used log DBH2*WD as predictor variables were the most accurate for BGB. It is concluded that these adjusted equations can be used to estimate the AGB and BGB in areas of the studied project. The adjusted equations can be recommended for use elsewhere in the region for forest stands of similar age, tree size ranges, species composition and site characteristics.

A restauração da Mata Atlântica vem recebendo aumento na atenção por causa do papel na conservação da biodiversidade e sequestro de carbono para a mitigação da mudança global do clima. Este estudo foi conduzido em um projeto de restauração da Mata Atlântica na região centro-sul do Estado de São Paulo - Brasil e buscou desenvolver equações alométricas para estimar a biomassa arbórea de espécies nativas em plantios mistos. Em 60 árvores de 19 espécies foram medidas a biomassa acima e abaixo do solo, o diâmetro do tronco (DAP: diâmetro a 1,3 m de altura), altura (H) e densidade específica da madeira (Ds). Diferentes equações de biomassa (linear e não linear) foram ajustadas para estimar a biomassa acima e abaixo do solo, utilizando DAP, H e Ds como variáveis preditoras. As equações de biomassa lineares foram as menos acuradas para a estimativa da biomassa acima e abaixo do solo. As equações de biomassa não lineares que usaram log DAP2, log H e log Ds como variáveis preditoras foram mais acuradas para a estimativa da biomassa acima do solo e as não lineares que usaram log DBH2*WD como variáveis preditoras foram as mais acuradas para a estimativa da biomassa abaixo do solo. Conclui-se que estas equações ajustadas podem ser usadas na estimativa da biomassa acima e abaixo do solo nas áreas do projeto estudado. Também pode ser considerado o uso destas equações ajustadas em outras áreas restauradas da Mata Atlântica com idade do povoamento, classes de tamanho das árvores, composição de espécies e características das áreas similares ao deste estudo, desde que árvores sejam avaliadas para verificar a eficácia da equação a ser usada.
Equações alométricas para estimativa da biomassa arbórea em plantios mistos com espécies nativas na restauração da Mata Atlântica
Keywords: Above-ground biomass; Below-ground biomass; Biomass equation; Tree allometry; Atlantic Forest; Restoration; Biomassa acima do solo; Biomassa abaixo do solo; Equação de biomassa; Alometria; Mata Atlântica; Restauração